STUDIES ON THE BIOMETRY AND BIOLOGY OF PENNAHIA ANEUS BLOCK - Gandhi, V (Indian Journal of Fisheries, 2011)
Biometry and biology of PennaMa aneus Bloch from Porto-Novo watersare discussed. The total length shows the fastest growth and the eye-diameter has .the lowest rate of growth. The food consists of fishes, Cymathoa Â«pp., prawns,prawn mysis and Squilla spp. The juyeniles feed predominantly on crustaceans.The presence of Cymathoa spp. in the stomach contents of adults indicates thatPennaMa aueus may exhibit cleaning association with other hosts of the parasite.The spawning takes place during a short period from September to October.PennaMa aneus attains sexual maturity at a length of 134 to 148 mm- Fecundityin the fish measuring 189 to 252 mm varies between J1423 and 79835